(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Biosimilars are biologic medical products that are highly similar to an already approved reference biologic, providing cost-effective alternatives while maintaining comparable safety and efficacy. The regulatory approval process for biosimilars differs from that of generic drugs because of the inherent complexity of biologics. Key regulatory agencies, including the U.S. FDA and the EMA, have established detailed guidelines for biosimilar approval that require a comprehensive program of analytical, non-clinical, and clinical studies. These studies are designed to demonstrate that the biosimilar is highly similar to the reference product with no clinically meaningful differences in safety, purity, or potency. The approval pathway may also address interchangeability, which permits pharmacy-level substitution without prescriber intervention, and allows extrapolation of indications based on existing scientific and clinical data. Post-market surveillance remains essential to monitor ongoing safety and efficacy. Despite scientific and regulatory complexities, biosimilar approval and market adoption continue to expand, driven by the demand for affordable biologic therapies and the expiration of patents on reference biologics.